First steps in the standardization of immunoglobulin IgG myeloperoxidase‐anti‐neutrophil cytoplasmic antibody measurements. (18th November 2015) - Hutu, D. P.; Tuddenham, E.; Monogioudi, E.; Meroni, P.; Schimmel, H.; Sheldon, J.; Zegers, I.; ,
Summary: The standardization of immunoassays for immunoglobulin (Ig)G myeloperoxidase‐anti‐neutrophil cytoplasmic antibodies (MPO‐ANCA) could contribute to a more accurate diagnosis and follow‐up of small vessels‐associated vasculitis, a systemic autoimmune disorder that leads to necrosis of blood vessel walls. Despite significant efforts by different groups, the level of comparability of results from commercially available immunoassays used for IgG MPO‐ANCA detection is still poor. Therefore, the potential for improvement using reference materials was assessed. The evaluation of a set of 30 patient samples with 11 assays showed that differences between assays result in different interpretations for individual patients. Only 10 of 30 patient samples had the same clinical interpretation among 11 assays applying the cut‐off values provided by each respective manufacturer. The correlation between results from 13 different assays was assessed in a pairwise manner. The correlation between results from patient samples was systematically very good for combinations of seven of those assays. The correlation of results ranged from reasonable to good for combinations with four other assays, therefore it should be possible to improve the comparability of results using a commutable reference material for calibration. Feasibility studies were conducted in order to find a reference material format most suitable for a calibrator. Two sets of candidate reference materials were produced from different raw materials, and assessed according to their suitability. A final format was selected, and a candidate reference material was produced.